2006
DOI: 10.1016/j.cub.2006.07.060
|View full text |Cite
|
Sign up to set email alerts
|

Congruent Embodied Representations for Visually Presented Actions and Linguistic Phrases Describing Actions

Abstract: The thesis of embodied semantics holds that conceptual representations accessed during linguistic processing are, in part, equivalent to the sensory-motor representations required for the enactment of the concepts described . Here, using fMRI, we tested the hypothesis that areas in human premotor cortex that respond both to the execution and observation of actions-mirror neuron areas -are key neural structures in these processes. Participants observed actions and read phrases relating to foot, hand, or mouth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
428
6
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 617 publications
(496 citation statements)
references
References 39 publications
41
428
6
10
Order By: Relevance
“…In line with our previous results (see also Pulvermüller et al, 2005a), the observed cross-talk between language and motor processes further emerged early following verb onset. Since words were displayed in the second half of the preparatory period, which is known to engage both premotor and primary motor cortex (Ball et al, 1999;Cui et al, 1999), our results are also consistent with neuroimaging studies that show activity in motor and premotor cortex during processing of action-related words or sentences (Aziz-Zadeh et al, 2006;Hauk et al, 2004;Tettamanti et al, 2005). Note that, in the present study, action verbs and concrete nouns differed both on action-relatedness and grammatical class.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with our previous results (see also Pulvermüller et al, 2005a), the observed cross-talk between language and motor processes further emerged early following verb onset. Since words were displayed in the second half of the preparatory period, which is known to engage both premotor and primary motor cortex (Ball et al, 1999;Cui et al, 1999), our results are also consistent with neuroimaging studies that show activity in motor and premotor cortex during processing of action-related words or sentences (Aziz-Zadeh et al, 2006;Hauk et al, 2004;Tettamanti et al, 2005). Note that, in the present study, action verbs and concrete nouns differed both on action-relatedness and grammatical class.…”
Section: Discussionsupporting
confidence: 91%
“…Two major models, the first based on Hebbian learning (Pulvermüller, 1996(Pulvermüller, , 2001(Pulvermüller, , 2005 and the second on the existence of the "mirror neuron system" (Fadiga & Craighero, 2004;Gallese & Lakoff, 2005;Rizzolatti & Arbib, 1998;Rizzolatti et al, 2001), suggest that processing of action words relies on activation of the motor programs used to perform, observe or simulate the actions referred to by words, either because of correlation learning (Pulvermüller, 2005) or because of a predisposition for imitation learning (Rizzolatti & Arbib, 1998). Evidence for such shared representations between word processing and sensory-motor information is provided by a large range of empirical data (Aziz-Zadeh et al, 2006;Boulenger et al, 2006;Boulenger et al, in press;Buccino et al, 2005;Glenberg & Kaschack, 2002;Glover et al, 2004;Hauk et al, 2004;Nazir et al, in press;Oliveri et al, 2004;Pulvermüller et al, 2005ab;Tettamanti et al, 2005;Zwaan & Taylor, 2006;see Fischer & Zwaan, in press, for a recent review). fMRI studies, for instance, have demonstrated somatotopic activation of motor and premotor cortices during processing of words or sentences referring to actions performed with arm, face or leg (AzizZadeh et al, 2006;Hauk et al, 2004;Tettamanti et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although there was some mu suppression throughout the whole coherent action sentence, we observed maximal mu suppression only when the action verb and the noun converged onto a concrete action. These results are in line with some embodiment theories, which claim that motor-related activation is context-dependent rather than purely lexical (Aziz-Zadeh et al, 2006;Boulenger et al, 2009;Schuil et al, 2013;Taylor et al, 2008). The fact that mu suppression effects were delayed until the second noun in the congruent action vs congruent perceptive contrast could indicate that understanding congruent perceptive sentences also elicits activation of motor assemblies, and only at the end of the congruent action sentence enough motor activation has been accumulated (mu suppression) to make the difference between the two conditions emerge sufficiently strongly to be detectable at the scalp.…”
Section: Time Course Of Mu Suppressionsupporting
confidence: 91%
“…Using abstract language as a contrasting condition for exploring motor related activity in action language is a common strategy in neuroimaging studies (Aziz-Zadeh et al, 2006;Tettamanti et al, 2005), and has also been used in a previous study of mu rhythm modulation (Moreno et al, 2013). In the latter study we also found strong evidence, based on mu suppression, that action language activates motor networks, whereas abstract language does not.…”
Section: Mu Suppression In Action Languagementioning
confidence: 58%
See 1 more Smart Citation